\(x^2+2x+5=\left(x^2+2x+1\right)+4=\left(x+1\right)^2+4\ge4\)Vậy GTNN của biểu thức là 4 khi \(x+1=0\Rightarrow x=-1\)
\(b,2x-x^2-4=-\left(x^2-2x+1\right)-3=-\left(x-1\right)^2-3\le-3\)Vậy GTLN của biểu thức là -3 khi \(x-1=0\Rightarrow x=1\)
a) Đặt \(A=x^2+2x+5\)
\(A=\left(x^2+2.x.1+1^2\right)+4\)
\(A=\left(x+1\right)^2+4\)
Ta có : \(\left(x+1\right)^2\ge0\forall x\)
\(\Leftrightarrow\left(x+1\right)^2+4\ge4\)
Vậy \(Min_A=4\Leftrightarrow x=-1.\)
b ) Đặt \(B=2x-x^2-4\)
\(B=-x^2+2x-4\)
\(B=-\left(x^2-2x+4\right)\)
\(B=-\left(x^2-2.x.1+1^2\right)+3\)
\(B=-\left(x-1\right)^2-3\)
Ta có : \(\left(x-1\right)^2\ge0\forall x\)
\(\Leftrightarrow-\left(x-1\right)^2\le0\forall x\)
\(\Leftrightarrow-\left(x-1\right)^2-3\le-3\)
Vậy \(Max_B=-3\Leftrightarrow x=1.\)
\(x^2+2x+5=x^2+2.x.1+1^2+4\)
\(=\left(x+1\right)^2+4\le4\)
Vậy GTLN của biểu thức là 4 khi x+1=0\(\Rightarrow\)x=-1
\(2x-x^2-4=-\left(x^2-2x+4\right)-\left(x^2-2.x.1+1^2-3\right)=\left(x-1\right)^2-3\le-3\)
Vậy GTLN của biểu thức là -3 khi x-1=0\(\Rightarrow\)x=1